Postkolonialni dialogi - Zakrajšek, Katja (Primerjalna književnost, 2007)
The paper presents some key theoretical perspectives on hybrid/dialogic phenomena and identities (mainly, but not exclusively, literray ones) emerging in so-called postcolonial spaces, attempting to sketch possibilities of plural, decentered readings of these phenomena.
Keywords: postkolonialne študije; hibridnost; dialoškost; kreolizacija; magični realizem; literarne študije